Sun Protection Behaviours in Skin Cancer Survivors: A Systematic Review and Meta‐Analysis - Shubham Kumar; Pratima Pandey; Asif Jan; Daniel Dubwa (JEADV Clinical Practice, 2026)
ABSTRACT Background Skin cancer, including melanoma and non‐melanoma skin cancer (NMSC), is one of the most prevalent cancers worldwide. Although sun protection behaviors, such as sunscreen use, protective clothing, and shade‐seeking, are crucial in preventing skin cancer recurrence and secondary malignancies, adherence to these behaviors among survivors remains suboptimal. Objectives This systematic literature review and meta‐analysis aim to examine the prevalence and associated factors of sun protection behaviors among skin cancer survivors. Methods A comprehensive search was conducted across PubMed, Embase, and Web of Science up to November 2025, using keywords related to skin cancer and sun protection. Studies were included if they reported the prevalence of sun protection behaviors or associated factors in skin cancer survivors. Data were extracted and analyzed using R software (version 4.4), and the quality of included studies was assessed using the Newcastle–Ottawa Scale. Results The review included 15 studies. The pooled prevalence of sunscreen use was 57% (95% CI: 0.51–0.63), wearing long sleeves was 48% (95% CI: 0.35–0.61), seeking shade was 58% (95% CI: 0.47–0.69), and using a hat with a brim was 46% (95% CI: 0.33–0.60). Factors influencing adherence included age, gender, education, perceived risk, and healthcare access. Melanoma survivors exhibited higher adherence to protective behaviors compared to those with NMSC. Limitations Most included studies relied on self‐reported data prone to bias, and high statistical heterogeneity was observed among the pooled estimates. Conclusions While many skin cancer survivors engage in sun protection, adherence remains inconsistent, particularly among specific demographic groups. Targeted interventions addressing demographic, psychosocial, and contextual factors are needed to improve sun safety practices and reduce skin cancer recurrence and secondary malignancies.